Fusion centers : counterterrorism information sharing concerns and deficiencies - Gerardi, Art M. (Intelligence and counterintelligence studies series., 2013)
Sharing terrorism-related information between state, local and federal officials is crucial to protecting the United States from another terrorist attack. Achieving this objective was the motivation for Congress and the White House to invest hundreds of millions of taxpayer dollars over the last nine years in support of dozens of state and local fusion centres across the United States. Congress directed the Department of Homeland Security (DHS) to lead this initiative. A bipartisan investigation has found, however, that DHS' work with those state and local fusion centres has not produced useful intelligence to support federal counter-terrorism efforts. This book offers recommendations to clarify DHS' role with respect to state and local fusion centres; to improve oversight of federal grand funds supporting fusion centres; conduct promised assessments of fusion centre information-sharing; and strengthen its protection of civil liberties in fusion centre intelligence reporting.